The resurgence of business process re-engineering in public sector transformation efforts: exploring the systemic challenges and unintended consequences - Vishanth Weerakkody (14150853) (2022)
The realisation of citizen-centric services in the public sector requires breaking traditional silos and transforming existing institutional structures and processes. Recent transformation efforts undertaken in government institutions have embraced business process re-engineering (BPR) concepts championed by the private sector over decades ago to facilitate such change. While public opinion continues to differ about these transformation efforts' success, there is little evidence to explain the influence of BPR on their success or failure. This paper explores BPR led public sector transformation efforts in two local authorities in Europe to evaluate the outcomes realised for both government and citizens. Empirical evidence reveals that while transformation efforts contributed towards improving efficiency and integrating processes across functions in the public sector, the institutional structures evolved into a collection of reshaped and newly formed siloes, which were distinctly focused on delivering a citizen-centric service. Other Information Published in: Information Systems and e-Business Management License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10257-021-00527-2